Legal Pluralism and The Dual Status of Catholic Divorce in Indonesia: Reformulating an Integrative Church Mediation Model for Harmonizing Civil and Canonical Jurisdictions - Diva Yulia Amanda; Afifah Kusumadara; Suhariningsih Suhariningsih (JURNAL AKTA, 2026)
This study aims to analyze the dualism of divorce status experienced by Catholics in Indonesia as a consequence of the normative conflict between national marriage law and Catholic Canon Law, as well as to formulate an integrative mediation model through Church institutions as a mechanism for harmonizing the two legal regimes. Existing studies have primarily focused on descriptive analyses of the relationship between state law and religious law, while limited attention has been devoted to procedural mechanisms capable of harmonizing conflicting civil and ecclesiastical jurisdictions. This normative legal research employs both statutory and conceptual approaches. The analysis is conducted through the examination of primary legal materials, including Law No. 1 of 1974 on Marriage, Government Regulation Number 9 of 1975, and the Code of Canon Law, supported by secondary legal materials from scholarly literature. Legal materials are analyzed using systematic and interdisciplinary interpretation methods. The findings reveal that the coexistence of civil divorce recognition under Article 38 of the Marriage Law and the principle of the absolute indissolubility of marriage under Canon 1141 generates a condition of legal dualism that reflects the characteristics of weak legal pluralism. This dualism gives rise to substantive legal uncertainty, ambiguity in personal status, restrictions on the civil right to remarry, and limitations on the exercise of religious rights within the Catholic Church. Consequently, the legal certainty provided by civil courts remains merely formal and administrative, without resolving the broader religious and social implications faced by Catholic divorcees. The novelty of this study lies in proposing an Integrative Church Mediation Model as a procedural harmonization mechanism that has not been comprehensively discussed in previous scholarship. The proposed model offers practical implications for judicial institutions, policymakers, and Church authorities in addressing legal uncertainty within Indonesia’s pluralistic legal system. The study concludes that a holistic procedural reconstruction is necessary through the adoption of an Integrative Church Mediation Model as a pre-litigation mechanism capable of harmonizing civil and ecclesiastical jurisdictions, thereby ensuring greater legal certainty, justice, and protection for Catholics in a pluralistic legal system.